X-ray microtomography reveals the 3D enzymatic deconstruction pathway of raw lignocellulosic biomass. (February 2023) - Blosse, S.; Bouchoux, A.; Montanier, C.Y.; Duru, P.
Abstract: In the context of the development of a circular bioeconomy, plant biomass constitutes a vast potential source of renewable molecules of interest. The industrial process essentially consists in using enzymes for its deconstruction. However, we are still lacking a precise understanding of the enzymes' action on such a complex, multiscale porous material. Here, we demonstrate that X-ray microtomography tackles this question in a unique way, making it possible to follow precisely the enzymatic degradation of a model biomass, wheat straw. We perform a thorough analysis of the imaging results over the full length scale of the sample and as a function of degradation time. In particular, we observe the progressive disappearance of specific cellulose-rich cell walls, with distinct 3D heterogeneities in the enzymatic action at different times and length scales. Those 3D pieces of information about the degradation process contrast clearly with those obtained from classical 2D imaging techniques. Graphical abstract: Unlabelled Image Highlights: 3D imaging of wheat straw sample by X-ray μCT, before and after enzymatic hydrolysis Enzymatic action imaged at different times and length scales The enzymatic action concentrates on parenchyma cell walls Extraction of markers for enzymatic degradation from 3D images Highlighting of the 3D heterogeneities of the enzymatic attack